Mother-Infant Bonding and Its Associated Factors Among Mothers in the Postpartum Period, Northwest Ethiopia, 2021 - Hailemeskel, Habtamu Shimels; Kebede, Alemwork Baye; Fetene, Metsihet Tariku; Dagnaw, Fentaw Teshome (Frontiers in Psychiatry, 2022)
Abstract Background: The emotional bond that a mother senses to her infant is essential to their social, emotional, and cognitive development. Understanding the level of mother-infant bonding plays an imperative role in the excellence of care. However, in Ethiopia, there is a paucity of information about mother-infant bonding in the postpartum period. Objective: This study aimed to assess the level of mother-infant bonding and its associated factors among mothers in the postpartum period, Debre Tabor Town Northwest Ethiopia, 2021 Methods: A community-based cross-sectional study was conducted with 422 postpartum mothers. The postpartum Bonding Questionnaire was used to assess mother-infant bonding. The Edinburgh Postnatal Depression Scale was used to assess postnatal depression. The level of marital satisfaction was assessed by using Kansas marital satisfaction scale. Social support was assessed by Oslo social support scale. A simple random sampling technique was applied to select study participants. Multiple linear regression were used to identify potential factors associated with the mother-infant bonding scale. A P-value of < 0.05 was considered to declare statistical significance. Results: In this study, 53 (12.6%) were having a risk for the quality of mother-infant bond difficulties between mother and an infant; 8.1% of mothers had a risk for rejection and pathological anger; 3.6% of mothers had a risk for infant-focused anxiety and 1.9% of mothers had risk for incipient abuse of an infant. Maternal depression status (adjusted β coefficient (β) = 2.31, 95% CI: (1.98, 2.64)), non-union marital status (β = 15.58, 95% CI: (9.88, 21.27)), being government employee (β = -5.68, 95% CI: (-9.71, -1.64)), having current pregnancy complication (β = -7.28, 95% CI: (-12.27, -2.29)), being non-breastfeeding mother (β = 7.66, 95% CI: (2.94, 12.38)), substance use history (β = -6.55, 95% CI: (-12.80, -0.30)) and social support (β = -2, 95% CI: (-2.49, -1.50)) were statistically significant factors for mother-infant bonding. Conclusion: Generally, a significant number of mothers had mother-infant bonding difficulties in the postpartum period. Preventing strategies for bonding difficulties focus on social support during pregnancy, screening postpartum mothers for postpartum depression, and special attention to substance users, nonunion maternal status, and non-breastfeeding mothers.